Effects of heat-treatment on the material properties of glass-ceramics samples fabricated by selective laser melting - Techanithisawat, Suphaphat (2017)
Selective laser melting is an additive manufacturing process that uses powder to fabricate geometrically complex parts with the help of computer-aided design. Despite the vast research on selective laser melting with metals, little is known for glass-ceramics. In this report, mechanical properties of a glass-ceramic - spodumene, subjected to heat-treatment is investigated. A series of experiments conducted includes heat-treatment, density measurement, x-ray diffraction analysis, and compression test.